Effect of thermal dose on heat shock protein expression after radio-frequency ablation with and without adjuvant nanoparticle chemotherapies. (16th November 2016) - Moussa, Marwan; Goldberg, S. Nahum; Kumar, Gaurav; Levchenko, Tatyana; Torchilin, Vladimir; Ahmed, Muneeb
Abstract: Purpose: The aim of this study was to evaluate the effect of different radio-frequency ablation (RFA) thermal doses on coagulation and heat shock protein (HSP) response with and without adjuvant nanotherapies. Materials and methods: First, Fischer rats were assigned to nine different thermal doses of hepatic RFA (50–90 °C, 2–20 min, three per group) or no treatment ( n = 3). Next, five of these RF thermal doses were combined with liposomal-doxorubicin (Lipo-Dox, 1 mg intravenously) in R3230 breast tumours, or no tumour treatment (five per group). Finally, RFA/Lipo-Dox was given without and with an Hsp70 inhibitor, micellar quercetin (Mic-Qu, 0.3 mg intravenously) for two different RFA doses with similar coagulation but differing peri-ablational Hsp70 (RFA/Lipo-Dox at 70 °C × 5 min and 90 °C × 2 min, single tumours, five per group). All animals were sacrificed 24 h post-RFA and gross tissue coagulation and Hsp70 (maximum rim thickness and % cell positivity) were correlated to thermal dose including cumulative equivalent minutes at 43 °C (CEM43 ). Results: Incremental increases in thermal dose (CEM43 ) correlated to increasing liver tissue coagulation (R 2 = 0.7), but not with peri-ablational Hsp70 expression (R 2 = 0.14). Similarly, increasing thermal dose correlated to increasing R3230 tumour coagulation for RF alone and RFA/Lipo-Dox (R 2 = 0.7 for both). The addition of Lipo-Dox better correlated to increasing Hsp70 expression compared to RFA alone (RFA: R 2 = 0.4, RFA/Lipo-Dox: R 2 = 0.7). Finally, addition of Mic-Qu to two thermal doses combined with Lipo-Dox resulted in greater tumour coagulation ( p < 0.0003) for RFA at 90 °C × 2 min (i.e. greater baseline Hsp70 expression) than an RFA dose that produced similar coagulation but less HSP expression ( p < 0.0004). Conclusion: Adjuvant intravenous Lipo-Dox increases peri-ablational Hsp70 expression in a thermally dependent manner. Such expression can be exploited to produce greater tumour destruction when adding a second adjuvant nanodrug (Mic-Qu) to suppress peri-ablational HSP expression.